Mitrofanoff Appendicovesicostomy in Robotic Paediatric Surgery—A Systematic Review - Diana Ronconi Di Giuseppe; Harry Claxton; Rauand Duhoky; Guglielmo Niccolò Piozzi; Jim S. Khan (Children)
Introduction: Proper bladder drainage is crucial. Children with bladder dysfunction may require alternative methods like clean intermittent catheterisation (CIC). However, CIC can be challenging for individuals with impairments. The Mitrofanoff procedure provides a solution by connecting the appendix to the bladder and creating a stoma on the skin, allowing for continent catheterisation. Minimally invasive techniques, including robotics, have been adopted recently. The aim of this study is to review the existing literature on robotic Mitrofanoff procedures. Materials and Methods: A systematic review on paediatric robotic Mitrofanoff procedures on the PubMed, Cochrane, and Scopus databases was conducted according to the PRISMA Statement. Critical appraisals of the included studies were performed with the Newcastle Ottawa Scale. Results: Six studies were included about the robotic Mitrofanoff procedure. Sex was reported in 50% of the studies. Ages were within the twelve-year age limit, as per the inclusion criteria. The mean operative time was 499.3 (±171.1) min. Four of the six studies reported a length of stay with a median of 6 days (±4; range 1.8–23). The incidence of complications was in line with established benchmarks. Only one study compared the Mitrofanoff procedure to open surgery, finding similar outcomes but longer operating times. Port placement and surgical strategy was described. Conclusions: Robotics can offer potential advantages for the Mitrofanoff procedure, despite its application still being in its early stages. This study emphasises the potential safety and efficacy of the robotic approach and promotes the need for further prospective high-quality studies.